COUPIERS: course pre-registration system / Zeti Darleena Eri ... [et al.] - Eri, Zeti Darleena; Abdul Latif, Mohd Hanapi; Ramlan, Mohd Atif; Jaafar, Ruhana; Syed Yasin, Sharifah Nurulhikmah; Mohamed, Hasiah; Yusoff, Sarah (2021)
In any academic institution, a timetable committees may consists of selected people of academics that are responsible in planning, operational decisions and executions of academic courses offer to students. Preparing a faculty’s timetable can be a difficult and complicated tasks for the timetable committees. The timetable preparation requires several numbers of meeting, identify requirements and accurate data acquires from students, new students intake and must comply with academic regulations. The practice can be trickier and exhaustive if programs have different academic structures to accommadate students backgrounds. Collecting data on courses to offer from students can be executed with more quicker and accurate using online system as compared to manually conducted. The Pre-registration Course System (COUPIERS) is a working online system developed to automate the process of gather data on courses that are required to offers in the coming semester starts. The data collected are critical so that the committees can prepare the initial process before allocate lecturers their academic loads. COUPIERS has executed it first run of the prototype. The results are expected in gathering data from assigned students to do pre-register courses as instructed by academic advisor before the semester ends. The data on courses were later used to assist committees in offering courses and amount classes to be opened or closed. With COUPIERS, data on courses to offer can be collected quicker, more accurate than manual process and can be stored in a database for future references. Finally, in any similar academic setting and structures, COUPIERS can also be used at any other campus or institutions.